Pension Deficits and the Design of Private Debt Contracts. (August 2019) - Balachandran, Balasingham; Duong, Huu Nhan; Vu, Van Hoang
Abstract : We find a positive relation between the amount of pension deficits and the cost of bank loans. The effect of pension deficits on the cost of bank loans is driven by financial constraints, information-asymmetry problems, and higher pension-investment risk. Banks tighten lending terms for firms with larger pension deficits by requiring collateral, increasing the number of loan covenants, and shortening loan maturity. Borrowers with larger pension deficits are also more likely to violate covenants in the future. Collectively, these findings indicate that pension deficits represent an additional source of risk priced by banks.